2022
DOI: 10.1002/ps.7053
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the current and future potential distribution of the bean bug Riptortus pedestris with increasingly serious damage to soybean

Abstract: BACKGROUND: The bean bug, Riptortus pedestris, has received intense attention in recent years because of its involvement in increasing outbreaks of staygreen syndrome in soybean (Glycine max (L.)), often causing almost 100% loss of soybean yield in China. However, for this pest of great economic importance, potential current and future distribution patterns and their underlying driving factors remain unclear.RESULTS: Maxent modelling under climate, elevation and land-use (including the distribution information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…Phytohormones, especially JA and SA pathways, are important signaling molecules in response to insect attack (Li et al ., 2006; Yates & Michel, 2018). The expression of SA‐ and JA‐related defense genes, such as LOX , FAD , PAL , and PR1 , is significantly induced when piercing–sucking insects, such as aphids and bugs, feed (Reddy et al ., 2013; Zhang et al ., 2020; H. Zhang et al ., 2022; Y. Zhang et al ., 2022). In addition, WRKY TFs, as important components in MAPK signaling pathways, are also significantly upregulated in response to insect feeding (Li et al ., 2012; Zhang et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phytohormones, especially JA and SA pathways, are important signaling molecules in response to insect attack (Li et al ., 2006; Yates & Michel, 2018). The expression of SA‐ and JA‐related defense genes, such as LOX , FAD , PAL , and PR1 , is significantly induced when piercing–sucking insects, such as aphids and bugs, feed (Reddy et al ., 2013; Zhang et al ., 2020; H. Zhang et al ., 2022; Y. Zhang et al ., 2022). In addition, WRKY TFs, as important components in MAPK signaling pathways, are also significantly upregulated in response to insect feeding (Li et al ., 2012; Zhang et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the insect releases various types of effectors that disturb the host plant defense response for better feeding (Bos et al ., 2010). For example, the aphid‐derived effector Sg2204 is involved in promoting host susceptibility by inhibiting the accumulation of both JA and SA, and decreases the expression levels of JA‐ and SA‐associated defense genes in wheat leaves (H. Zhang et al ., 2022; Y. Zhang et al ., 2022). Our results showed that multiple biological processes were affected by R. pedestris feeding on soybean, including the immune pathway, photosynthesis, and plant hormone signal transduction (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In recent years increased attention has been paid to this pest due to its potential to cause soybean Zhengqing, which is a staygreen syndrome that has resulted in yield losses from 0% to nearly 100% in the Huang-Huai-Hai River basin in China. 17,18 R. pedestris primarily acquires nutrients by utilizing its specialized mouthparts to puncture the pods and seeds. 19 Considering that soybean seeds are rich in lipid content, the insects perhaps depend on lipases to facilitate feeding, digestion, and reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…During feeding, R. pedestris inserts its sucking mouth into the tissues of the host plant to acquire water and nutrients, resulting in a reduction in soybean yield and seed quality (Bae et al, 2014;Fu et al, 2021). In recent years, soybean staygreen syndrome has expanded rapidly in soybean-growing areas in China (Zhang et al, 2022). However, the mechanisms by which R. pedestris causes soybean staygreen syndrome remain obscure.In nature, plants and herbivorous insects have been engaged in a co-evolutionary arms race (Erb et al, 2012;Stahl et al, 2018).Hemipterans, including R. pedestris, are major pests on crops, causing plant damage by piercing crop plants with their needle-like mouthparts.…”
mentioning
confidence: 99%